Feasibility of a Bone Mineral Measurement Technique Based on Coherent Scattering of Gamma Rays - Ndlovu, Alois Marshall N. (My University, 1990)
The investigation of the feasibility of a bone mineral measurement technique based on coherent scattering of gamma rays was performed using a HPGe detector.
Considerations of detector efficiency and resolution, absorbed dose to bone, spectral separation between coherent and Compton peaks, variation of differential coherent cross section and scattering volume with scattering angle led to the selection of a photon soruce energy of 103.2 keV (Sm153) and a scattering angle of 40 degree.
Bone phantoms (aqueous solutions of K2HPO4) were used to examine how the coherent intensity emanating from a scattering volume at the centre of an object varied with object dimensions and solution effective atomic number. Simulation and experimental measurements with solutions in cylindrical polyethylene containers of varying sizes indicated that the ratio of the coherent count rate to the transmission count rate was independent of container dimensions (at least up to 7 cm diameter). For ease of comparison, all the ratios at different concentrations were normalised to that of water obtained in an identical measurement geometry. The normalised coherent-to-transmission ratios were related to solution effective atomic number by a power function with a exponent of 3.30 plus minus 0.15.
When the rate of change of the normalised ratio with effective atomic number is used as an indicator of the sensitivity of the technique, the coherent-to-transmission method is almost twice as sensitive as a coherent-to-Compton technique.
In-citro bone mineral measurements were made in the calcaneus (heel bone), an easily accessible site in which 90% of bone mineral is trabecular. Prior to the measurements the spatial distribution of mineral was investigated with a Norland 278-A single photon absorptiometry (SPA) machine in slices of several calcanei. Cortical bone was restricted to a thin peripheral region of the calcaneus.
Three whole calcanei, one of which had its calcium content deliberately reduced by soaking overnight in hydrochloric acid, were selected for measurement using the coherent-to-transmission technique. For the first measurement each bone was submerged in water only. For the second measurement the trabeculae were filled with corn oil, to simulate marrow fate, and again each bone were submerged in water. The latter measurements were about 50% lower than the first, indicating a large "marrow fat" effect. However, both sets of results can by explained by assuming a power relationship between the normalised coherent-to-transmission ratio and the effective atomic number of the scattering volume contents.
Cuboid samples of side approximately 16 mm were cut out of the posterior region of each calcaneus and ashed. A plot of the normalised coherent-to-transmission ratio versus the ashed weight per unit volume (bone mineral density) of the three calcanei yielded a straight line. While this indicates that the normalised coherent-to-transmission ratio is an indicator of bone mineral, a larger number of samples will be required to establish a robust calibration curve.
Keywords: Biological and Chemical Physics; Biological and Chemical Physics